Moderating Effects of Resilience on Depression, Psychological Distress, and Suicidal Ideation Associated With Interpersonal Violence - Fedina, Lisa (Journal of interpersonal violence, 2021)
Resilience has been found to attenuate the effects of negative mental health symptomology associated with interpersonal victimization; however, existing research has largely focused on resilience traits, such as individual cognitive and environmental factors that promote resilience. In addition, empirical knowledge on the extent to which resilience mitigates suicidal symptomology associated with interpersonal violence victimization is particularly limited. This study assesses whether the relationship between interpersonal violence (i.e., IPV and nonpartner sexual violence) and mental health symptomology (i.e., depression, psychological distress, and suicidal ideation) is moderated by resilience using a general population sample of women (N = 932). A cross-sectional, observational survey was administered in four U.S. cities (Baltimore, New York City, Philadelphia, and Washington, D.C.). Bivariate results indicated that women exposed to interpersonal violence reported significantly higher rates of suicidal ideation, depression, and psychological distress compared with women without exposure to interpersonal violence. Regression models revealed significant positive associations between interpersonal violence and depression, distress, and suicidal ideation, adjusting for sociodemographics. Resilience did not significantly moderate the relationship between interpersonal violence victimization and any associated mental health outcomes. However, subgroup analyses reveal significant interaction effects between resilience and IPV within specific racial and ethnic minority subgroups, suggesting that attenuating effects of resilience on mental health symptoms (i.e., depression and psychological distress) associated with IPV likely vary across race and ethnicity. Implications for future research and clinical interventions focused on resilience among survivors of interpersonal violence are discussed.